Pengelolaan Lahan Basah Terpadu di Desa Mulia Sari Kecamatan Tanjung Lago, Kabupaten Banyuasin - Ombun Rahmi; Robiyanto Hendro Susanto; Ari Siswanto (Institut Pertanian Bogor, 2015)
Lowland is the fragile land which is sensitive toward modification. The accurate and integrated management is substantially needed to utilize the lowland. This study analyzed the integrated lowland management in Mulia Sari Village, Tanjung Lago Subdistrict, Banyuasin Regency, South Sumatera Province. Sampling was chosen randomly consisted 21 respondens. Primary data: the farmers typical and farming system, were collected by using questionnaire while doing observation and purposive interviewing method. Qualitative approach was used to analyze the data. The result represented that the farmers typical substially determine the integrated lowland management. 80% people in Mulia Sari Village are farmers. Average farmers are between 25-65 years old. 75% farmers are male which is higher than female farmers that is 4.7%. More or less 50% farmers do not comply nine years learning programme. 33% of farmer’s educational level was only elementry school. Approximately, 47.61% graduated junior high school. They got land between 0.5-4 acre and more than 30% rented. The farming system of lowland need to consider water and land management. Both water and land management are the primary requirement in the integrated lowland management. The integrated lowland management in Mulia Sari Village is hardly to apply. It still needs strategic policy and elucidation which are compatible with the farmer’s typical and the lowland ecosystem.